Art, equality and learning pedagogies against the state - Atkinson, Dennis 1947- (SensePublishers, 2011)
In this book the notions of real learning and equality are approached as processes of becoming leading to the figuration of new worlds through local curations of learning and practice. Though its main theses are mainly grounded in the context of art practice and education they have a much wider application to other (perhaps all) contexts of learning through the notions of pedagogies against the state and pedagogies of the event. Learning is conceived as a political act rather than, for example, an incremental process of psychological or sociological development.